How Well Are Sudden Stratospheric Warming Surface Impacts Captured in CMIP6 Climate Models? - Hall, Richard J.; Mitchell, Dann M.; Seviour, William J.M.; Wright, Corwin J. (Journal of Geophysical Research: Atmospheres, 2022)
Sudden stratospheric warmings (SSWs) are associated with episodes of extreme winter weather, often leading to significant societal impacts. Using observations alone, it is hard to quantify the SSW impact on surface extreme weather, because the observational record only covers ∼40 events. Climate models provide an effective way to increase this sample size, potentially into 1000s of events, but only if we trust that they capture SSW processes well. We evaluate the representation of stratosphere-troposphere coupling associated with SSWs in 10 models from the sixth Coupled Model Intercomparison Project (CMIP6). In general, the models and the reanalysis have different patterns of tropospheric precursors, but similar stratospheric responses to precursors. The individual CMIP6 models capture the main spatial features of surface impact: A negative phase of the Northern Annular Mode (NAM), with distinctive alternating positive and negative temperature anomalies across the northern hemisphere. We assess the time evolution of SSW surface impacts for individual models over different regions and construct an overview of how well each model captures surface impacts. Models perform particularly well in simulating the surface impact evolution over the Baffin Bay and Siberia regions. Over the United States, Northwest Europe, and the Middle East, there is less agreement among models. Models underestimate the magnitude of temperature anomalies associated with SSWs over the Middle East and over the Eastern Seaboard of North America, but the magnitude of the circulation responses are comparable with reanalysis.